2010
DOI: 10.4269/ajtmh.2010.10-0052
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Full-Length Genomic Sequences of 10 Dengue Serotype 1 Viruses Associated with Different Genotypes, Epidemics, and Disease Severity Isolated in Thailand over 22 Years

Abstract: Abstract. Comparative sequence analysis was performed on the full-length genomic sequences of 10 representative dengue virus serotype 1 (DENV-1) strains sampled from patients at Children's Hospital, Bangkok, Thailand over a 22-year period, which represented different epidemics, disease severity, and sampling time. The results showed remarkable inter-genotypic variation between predominant and non-predominant genotypes and genotype-specific amino acids and nucleotides throughout the entire viral genome except f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 59 publications
(66 reference statements)
1
13
0
Order By: Relevance
“…These studies suggested adaptive evolution of DENV in natural populations but indicated that the adaptive selection pressures differ among serotypes, genotypes and the encoded proteins of the virus. Furthermore, fixation of beneficial mutations may lead to virus evolution with altered antigenicity, virulence, or tissue tropism; and eventually influence disease patterns and transmission [17]. Similarly, genetic recombination is also a significant factor in diversity of DENV in natural populations [18].…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggested adaptive evolution of DENV in natural populations but indicated that the adaptive selection pressures differ among serotypes, genotypes and the encoded proteins of the virus. Furthermore, fixation of beneficial mutations may lead to virus evolution with altered antigenicity, virulence, or tissue tropism; and eventually influence disease patterns and transmission [17]. Similarly, genetic recombination is also a significant factor in diversity of DENV in natural populations [18].…”
Section: Introductionmentioning
confidence: 99%
“…Dengue virus is a surprisingly conserved RNA virus (Choudhury, Lott, Banu, Cheng, & Teo, ; Lequime, Fontaine, Ar Gouilh, Moltini‐Conclois, & Lambrechts, ; Thai, Henn, Zody, Tricou, & Nguyet, ; Amarilla, de Almeida, Jorge, Alfonso, & de Castro‐Jorge, ; Holmes, ). Even though its serotypes present seemingly competitive dynamics, similar to the behaviour of antigenic strains of other fast evolving pathogens, observations of positive selection are rare (Tang et al., ; Filomatori et al., ; Waman et al., ; Hang et al., ; Choudhury et al., ; Martin, Chirivella, Co, Santiago, & Gubler, ; Sim, Aw, Wilm, Teoh, & Hue, ). Dengue transmission models have offered insight, but have so far failed to reach consensus on the possible biological drivers of the observed dynamic behaviour.…”
Section: Challenges and Opportunities In Computational Researchmentioning
confidence: 99%
“…There are also reports of sporadic episodes of positive selection and fixation of particular lineages (Tang et al., ; Filomatori et al., ; Waman et al., ; Hang et al., ; Choudhury et al., ; Martin et al., ), and it is generally believed that most events of lineage replacement go unnoticed, as the majority of endemic regions rely on syndromic surveillance, and as these events are not expected to result in significant changes in disease incidence (Lourenço & Recker, ). While there are rare examples of well‐described lineage shifts in the literature (OhAinle et al., ; Bennett, Holmes, Chirivella, Rodriguez, & Beltran, ), not much is known about the epidemiological and ecological contexts in which emergence of fitter lineages is favoured.…”
Section: Challenges and Opportunities In Computational Researchmentioning
confidence: 99%
See 2 more Smart Citations